THE ROLE OF NONVERBAL MEANS IN EXPRESSING PSYCHOLOGICAL STATES IN LITERARY TEXTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This study examines the integral role of nonverbal means in communication, emphasizing their significance alongside verbal tools. Nonverbal communication encompasses gestures, facial expressions, vocal tone, and body language, playing a critical role in enhancing the emotional impact, clarifying messages, and complementing verbal communication. The paper explores the classification, functions, and application of nonverbal tools in various contexts, including psycholinguistic studies and literary narratives. It highlights how nonverbal means are used to reflect emotions, psychological states, and situational nuances, contributing to a more comprehensive understanding of communication dynamics.